In situ monitoring system in the dry corridor of Guatemala through the establishment of a digital agricultural plot /Sistema de monitoreo in situ en el corredor seco de Guatemala a través del establecimiento de una parcela agrícola digital - Martínez, Jesús David; Jimenez, Daniel Ricardo; Ramos, Gresia Dalal; Estrada Vargas, Oscar H; Muñoz, Luis Armando; Van Loon, Jelle Filip; Bonilla, Melissa; Muller, Anna (2023)
The In-situ Monitoring System in the Dry Corridor of Guatemala represents a testing ground for automated agricultural. Located in the region's challenging dry corridor, this innovative plot, supported by CGIAR, CUNORI University, and the CGIAR initiatives on Digital Innovation and AgriLac, is designed to enhance decision-making and efficiency for small-scale farmers. It achieves this through advanced in situ sensors and technologies that deliver precise data on climate and soil conditions. The plot functions as a laboratory, testing technologies that are apt for the unique challenges of the dry corridor, with a focus on social, environmental, and economic efficiency, while also addressing the needs of the regional community. Conducting user research is crucial, serving as a compass to guide our actions. This pioneering laboratory aims to optimize agri-food systems and expand the model, benefiting farmers in Guatemala and potentially in other countries, through the advancement of digital technology.